SOME ASPECTS OF COMMUNITY-ACHILLED PNEUMONIA IN CHILDREN - Ibatova Sh.M.; Abdurasulov F.P.; Ruzikulov N.E. (American Journals, 2023)
Predisposing factors for the development of pneumonia in young children are perinatal pathology, congenital defects of the heart and other internal organs, rickets, atopic dermatitis, hypovitaminosis and deficiency conditions, including immunodeficiencies. We examined 116 patients aged 3 months and over. up to 3 years old who applied to a family clinic with community-acquired pneumonia. Patients studied complaints, anamnestic data, clinical symptoms, analyzed the results of laboratory and instrumental research methods and developed recommendations for hospitalization of sick children with acute pneumonia in the hospital. The article presents the results of observation of patients with community-acquired pneumonia and treatment on an outpatient basis, data from clinical, radiological and laboratory studies and indications for hospitalization. Thus, timely diagnostics, complex treatment community-acquired pneumonia on an outpatient basis and the development of recommendations for hospitalization in a hospital significantly improve the prognosis of community-acquired pneumonia.
Keywords: Pneumonia, diagnosis, treatment, patients, respiratory failure, hypovitaminosis.